E-001 TARGET Intracranial Aneurysm Coiling Prospective Multicenter Registry: Initial Periprocedural Results in 120 Patients. (26th July 2014) - Zaidat, O; Castonguay, A; Puri, A; Rai, A; Badruddin, A; Mack, W; Alshekklee, A; Shah, Q; Hussain, S; Kabbani, M; Bulsara, K; Taqi, M; et al.
Abstract : Background and purpose: To describe the periprocedural results of the TARGET Registry, an on-going, prospective, non-randomised, multicenter, real-world study of patients with ruptured or unruptured intracranial aneurysms that are embolised with the new generation TARGET Coils. In particular, the aneurysm that were coiled with 100% 360 complex coils only were compared to the aneurysm that were coiled with mixed 360 and helical coil or helical coils only. Methods: Patients with de novo untreated ruptured or unruptured intracranial aneurysms were embolised with either TARGET 360° or Helical coils in 13 US centers. The primary outcome, aneurysm packing density (PD), was assessed at immediate post-procedure. Analysis was by per protocol. The secondary outcomes were modified Rankin's Scale (mRS) at discharge and the influence of use of 100% 360 coils on clinical and angiographic outcomes. JMP statistical software was used for analysis. Results: 120 patients enrolled to date were eligible for this per protocol analysis. 51 (42.5%) patients with ruptured and 69 (57.5%) with unruptured aneurysms were treated. Mean age was 58.1 ± 13.04 years; 75.6% female, 73.3% white. TARGET 360° coils was used in 60.5%, mixed 360° and Helical Coils in 35.1%, and TARGET Helical Coils in 4.4% of the cases. Immediate complete occlusion rate was seen in 84.4% of the cases. Packing density was the main predictor of complete occlusion (mean PD 28.7 ± 18.1 in those with complete occlusion vs. 20 ± 12, p-value 0.005). Mean PD was 25.4 ± 16.3%. Multivariate analysis showed maximum aneurysm size (p value 0.0001), and use of stent (p value 0.02) to be independent predictors of PD. In-hospital mortality was 0.8% (1/120) and discharge good outcome (mRS 0–2) was seen in 110/120 (91.7%). Poor outcome occurred in 13.7% of the ruptured aneurysm and 4.4% of the unruptured aneurysms. Predictors of discharge outcome included age, rupture presentation, aneurysm neck size, and occlusion grade. Conclusion: In this prospective and core lab adjudicated multicenter Target aneurysm registry, the mean PD was 25.4 ± 16.3% and was the main predictor of complete aneurysm occlusion. Poor outcome was 4.4% in the unruptured aneurysm and 13.7% in the ruptured aneurysms. Predictor of outcome at discharge included age, rupture status, aneurysm occlusion, and aneurysm neck size. Disclosures: O. Zaidat: None. A. Castonguay: None. A. Puri: None. A. Rai: None. A. Badruddin: None. W. Mack: None. A. Alshekklee: None. Q. Shah: None. S. Hussain: None. M. Kabbani: None. K. Bulsara: None. M. Taqi: None. V. Janardhan: None.